1999
DOI: 10.1007/s002130051107
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of nicotine on attentional processes

Abstract: The results are consistent with the hypothesis that nicotine mainly improves the intensity feature of attention, rather than the selectivity feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 21 publications
8
61
0
2
Order By: Relevance
“…In normal human subjects, nicotine administration has consistently been shown to enhance attention by reducing omissions . This is consistent with the hypothesis of Mancuso et al (1999), whereby the nicotine-induced improvement in attention is a consequence of nicotine acting to 'lock the brain into the attentional processing mode and so there are fewer lapses in attention', hence fewer errors of omission might be expected. However, an improvement in accuracy (proportion correct) following nicotine administration has also been observed in subjects displaying impaired attentional function, associated with schizophrenia, Alzheimer's disease, and attention deficit hyperactivity disorder (White and Levin, 1999;Shytle et al, 2002;Yang et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In normal human subjects, nicotine administration has consistently been shown to enhance attention by reducing omissions . This is consistent with the hypothesis of Mancuso et al (1999), whereby the nicotine-induced improvement in attention is a consequence of nicotine acting to 'lock the brain into the attentional processing mode and so there are fewer lapses in attention', hence fewer errors of omission might be expected. However, an improvement in accuracy (proportion correct) following nicotine administration has also been observed in subjects displaying impaired attentional function, associated with schizophrenia, Alzheimer's disease, and attention deficit hyperactivity disorder (White and Levin, 1999;Shytle et al, 2002;Yang et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Nicotine, the predominant psychoactive compound in tobacco smoke, has been shown to enhance sustained attention in normal humans by reducing omission levels . Moreover, it has been suggested that nicotine can lock the brain into an attentional processing mode whereby there are fewer lapses in attention and therefore less omissions (Mancuso et al, 1999). These observations may underlie the ability of nicotine to enhance attention and improve the symptomatology of various human diseases including schizophrenia (Yang et al, 2002), Alzheimer's disease (White and Levin, 1999), attention deficit hyperactivity disorder (Shytle et al, 2002), Parkinson's disease (O'Neill et al, 2002), and Tourette's syndrome (Sanberg et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of nicotine to abstinent smokers improves general alertness, attention, and vigilance [4,5]. Nicotine improves performance on vigilance tasks [6,7], inhibition of prepotent responses [8], and verbal learning [9] in nonsmokers. Effects such as these, however, are thought to reflect an influence on general alertness, rather than the primary influence of specific cognitive domains [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…While enhanced performance on the Stroop Task (ie, reduced Stroop effect) after cigarette smoking has been observed in abstinent smokers (412 h) (Mancuso et al, 1999;Pomerleau et al, 1994), it was not clear whether this effect was due to relief from nicotine withdrawal, a facilitating effect of nicotine on selective attention (beyond the preabstinence level), or a combination of both (for review see Heishman et al (1994)). Some studies found that administration of nicotine per se (Provost and Woodward, 1991) or cigarette smoking (Hasenfratz and Battig, 1992;Provost and Woodward, 1991) decreased the Stroop effect in nonsmokers (Provost and Woodward, 1991) or smokers smoking ad libitum (Hasenfratz and Battig, 1992;Provost and Woodward, 1991).…”
Section: Introductionmentioning
confidence: 99%